The Body Weight Alteration and Incidence of Neoplasm in Patients With Type 2 Diabetes: A Meta-Analysis of Randomized Controlled Trials - Lin, Chu; Cai, Xiaoling; Yang, Wenjia; Lv, Fang; Nie, Lin; Ji, Linong (Frontiers in Endocrinology, 2020)
Objective Whether hypoglycemic treatments with weight-alternating effects influence the incidence of neoplasm in type 2 diasbetes (T2D) remains uncertain. Therefore, we performed a meta-analysis to assess the association between the weight alteration and incidence of neoplasm in patients with T2D. Research Design and Methods Systematic searches were conducted for studies published between the inception of 1950s and September 2019. Randomized controlled trials conducted in T2D patients with at least 48-week follow-up, significant weight change difference between treatment arms and reports of neoplasm events were included. Fixed-effects model and meta-regression analysis were accordingly used. Results In all, 46 studies were included. Analysis indicated weight reduction was not associated with a decreased incidence of neoplasm (OR = 1.01, 95% CI, 0.96 to 1.07, I2 = 17%) and weight elevation was not associated with an increased incidence of neoplasm (OR = 0.91, 95% CI, 0.76 to 1.09, I2 = 0%). Meta-regression analysis showed a slower weight reduction rate (β = −5.983, 95% CI, −11.412 to 0.553, P = 0.03) instead of weight change difference (β = −0.030, 95% CI, −0.068 to 0.007, P = 0.115) was significantly associated with reduced risk of neoplasm in patients with T2D. Moreover, a decreased incidence of prostate, bladder, and uterine neoplasm was observed in T2D patients with weight reduction difference while an increased incidence of thyroid neoplasm was found in glucagon-like peptide-1 receptor analog (GLP-1RA) users with weight reduction difference. Conclusions Additional weight change achieved by current hypoglycemic agents or strategies in short and medium periods was not associated with incidence of most neoplasm in patients with T2D. However, a decreased incidence of prostate, bladder, and uterine neoplasm was shown in T2D patients with weight reduction difference while an increased risk of thyroid neoplasm was observed in T2D patients on GLP-1RA treatments with weight reduction difference. A more sustained and persistent weight reduction process may confer reduced risk of neoplasm in patients with T2D.